以資訊處理觀點論Metadata之本質與意涵 From Information Processing to the Essence of Metadata - Shien-chiang Yu (Jiàoyù zīliào yǔ túshūguǎn xué, 2007)
Metadata最普遍的解釋是「data about data」，但這一個解釋太過於簡單與籠統，對此一概念的傳遞不僅有限且容易被誤解。由於metadata在電子環境已運行多年，以致其內涵在不同資訊處理與應用領域具備不同的意義。因此，本文嘗試從資訊處理角度討論metadata之功能與作用、字根延伸意義、語法及結構模式三個不同應用的角度分析metadata的內涵，藉以歸納適合的定義，並透過現有國內中文譯名的文字字義，探討中譯的適切性，提供使用者對metadata此一字彙與內涵能有更詳細了解與應用。 The most common definition for metadata is “data about data”. However, this expression is rather simple and ambiguous. It is also insufficient and easy to be misunderstood. Metadata has already been used widely in the past years in the electronic environment, thus researchers and practitioners have come up with various meanings for metadata on different information applications. This paper analyzes three perspectives of metadata from the domain of information processing, including function, literal, syntax and structure. The paper, therefore, concludes with appropriate definitions for each of the three views of metadata. In addition, this paper discusses the popular Chinese translations of metadata and their appropriateness. It is believed that clear definitions for metadata in different scenarios will eventually help users to understand the term and its applications better.